Differences in maternal and early child nutritional status by offspring sex in lowland Nepal. Issue 3 (6th July 2021) - Saville, Naomi M.; Harris‐Fry, Helen; Marphatia, Akanksha; Reid, Alice; Cortina‐Borja, Mario; Manandhar, Dharma S.; Wells, Jonathan C.
Abstract: Objective: On average, boys grow faster than girls in early life but appear more susceptible to undernutrition. We investigated sex differences in early child growth, and whether maternal nutritional status and diet differed by offspring sex during and after pregnancy in an undernourished population. Methods: We analyzed longitudinal data from a cluster‐randomized trial from plains Nepal, stratifying results by child or gestational age. Children's outcomes (0–20 months) were weight, length, and head circumference and their z ‐scores relative to WHO reference data in 2‐monthly intervals (n range: 24837 to 25 946). Maternal outcomes were mid‐upper arm circumference (MUAC), and body mass index (BMI) during pregnancy (12–40 weeks) ( n = 5550 and n = 5519) and postpartum (n = 15 710 and n = 15 356), and diet in pregnancy. We fitted unadjusted and adjusted mixed‐effects linear and logistic regression models comparing boys with girls. Results: Boys were larger than girls, however relative to their sex‐specific reference they had lower length and head circumference z ‐scores from birth to 12 months, but higher weight‐for‐length z ‐scores from 0 to 6 months. Mothers of sons had higher MUAC and BMI around 36 weeks gestation but no other differences in pregnancy diets or pregnancy/postpartum maternal anthropometry were detected. Larger sex differences in children's size in the food supplementation study arm suggest that food restriction in pregnancy may limit fetal growth of boys more than girls. Conclusions: Generally, mothers' anthropometry and dietary intake do not differ according to offspring sex. As boys are consistently larger, we expect that poor maternal nutritional status may compromise their growth more than girls. Copyright © 2021 John Wiley & Sons, Ltd.